Equine Anthelmintic Resistance: Horse Owner and Yard Manager Perception of the Barriers Affecting Strategic Control Measures in England - Faye E. McTigue; Stephen C. Mansbridge; Alison Z. Pyatt (Veterinary Sciences, 2022)
Equine anthelmintic resistance poses a threat to the health and welfare of horses worldwide. With no new imminent anthelmintic classes, it is vital to decrease the resistance rate and preserve available classes. Traditional indiscriminate anthelmintic use is not synonymous with a strategic control ideology; however, many continue to implement outdated practices. In comparison to livestock farmers, there have been few social science studies examining horse owner behaviours. This study aimed to understand the perceived barriers faced by horse owners and yard managers to adopting a strategic approach to helminth control, and to explore their experiences. Semi-structured interviews permitted the exploration of the stakeholders’ beliefs, opinions, experiences, attitudes, and behaviours. Personal resources, internal influences, and external influences were identified by participants as the barriers to adoption of strategic controls. Two further themes impacting effective implementation of strategic controls emerged surrounding helminth information and source, as well as accurate dosing. Challenges associated with anthelmintic administration and bodyweight estimation suggest that inaccurate dosing is prevalent. Industry-wide implementation of a single ‘best practice’ could support prescriber decision-making to encourage uptake of effective strategic helminth controls. The barriers identified in this study could help influence guidance given to horse owners through a better understanding of their beliefs and behaviours.